2020
DOI: 10.1111/nep.13703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic kidney disease on mortality and cardiovascular outcomes after acute coronary syndrome: A nationwide data linkage study (ANZACS‐QI 44)

Abstract: Aims Chronic kidney disease (CKD) is associated with an increased risk of cardiovascular disease (CVD). We examined the characteristics, management and outcomes of patients with CKD in the All New Zealand Acute Coronary Syndrome Quality Improvement (ANZACS‐QI) national registry. Methods The cohort comprised New Zealand (NZ) patients with an acute coronary syndrome undergoing coronary angiography between January 2013 and December 2016. Patients were categorized according to their stage of CKD. Outcomes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Since the eGFR range in our sample was close to what is considered a normal renal function (age 64.9 ± 12.3, eGFR 62.1–96.7) it is reasonable to postulate that dysregulation of TCA cycle metabolism has preceded the development of kidney disease ( 9 ). Given that declined renal function is presented after ACS and is one of the main risk factors for cardiovascular outcomes and mortality ( 37 ), our results suggest that TCA cycle metabolites are associated with higher risk of clinical outcomes following ACS possibly due to renal decline. The causative mechanisms by which impaired kidney function contributes to cardiovascular diseases are not fully elucidated.…”
Section: Discussionmentioning
confidence: 75%
“…Since the eGFR range in our sample was close to what is considered a normal renal function (age 64.9 ± 12.3, eGFR 62.1–96.7) it is reasonable to postulate that dysregulation of TCA cycle metabolism has preceded the development of kidney disease ( 9 ). Given that declined renal function is presented after ACS and is one of the main risk factors for cardiovascular outcomes and mortality ( 37 ), our results suggest that TCA cycle metabolites are associated with higher risk of clinical outcomes following ACS possibly due to renal decline. The causative mechanisms by which impaired kidney function contributes to cardiovascular diseases are not fully elucidated.…”
Section: Discussionmentioning
confidence: 75%
“…До них слід віднести: вік, коморбідність, супутні захворювання -артеріальна гіпертензія (АГ), цукровий діабет (ЦД), ожиріння тощо [1]. Особливо слід виділити функціональний стан нирок, що може розглядатись, з одного боку, як маркер прогнозу цілої низки серцево-судинних захворювань, з іншого боку,саме супутні захворювання серцево-судинної системи, ЦД, АГ впливають на перебіг та прогресування захворювань нирок [2]. Швидкість клубочкової фільтрації (ШКФ) є раннім та чутливим маркером функціонального стану нирок та може використовуватись як для діагностики, так і для прогнозування перебігу серцево-судинних захворювань [3].…”
Section: Discussionunclassified
“…Many studies have reported an increased risk of death, myocardial infarction, stroke, and major bleeding in chronic kidney disease, especially in its most severe stages[ 66 ]; thus, preventing renal deterioration and preserving its function may be a key element in the management of transplanted patients.…”
Section: Renal Dysfunctionmentioning
confidence: 99%